Soal pilihan ganda yang valid dan reliabel untuk menginterpretasikan keterampilan berpikir siswa SMP - Arifin Riadi; Noor Laila Atini (STKIP PGRI Banjarmasin, 2018)
This study aims to obtain good multiple choice questions, viewed from valid and reliable. Validity test used in this study is Pearson correlation test, and reliability testing using Cronbach alpha. The draft of the questions was 24, with the proportion of each level of thinking skill represented by 4 questions. The level of thinking skill in question is based on the revised version of Bloom's taxonomy namely Remembering, Understanding, Applying, Analyzing, Evaluating, and Creating. Each question has four answer choices according to the provisions for junior high school students. From the results of the trial and data analysis, it was found that there were 16 valid and reliable questions, with an overall reliability score of 0.602. The results of this study are expected to be used to obtain an overview of the level of thinking skills of junior high school students in schools and in other regions.